Temporary threshold shift after impulse-noise during video game play: Laboratory data - Spankovich, C. (Int J Audiol, 2014)
OBJECTIVE: Prevention of temporary threshold shift (TTS) after laboratory-based exposure to pure-tones, broadband noise, and narrow band noise signals has been achieved, but prevention of TTS under these experimental conditions may not accurately reflect protection against hearing loss following impulse noise. This study used a controlled laboratory-based TTS paradigm that incorporated impulsive stimuli into the exposure protocol; development of this model could provide a novel platform for assessing proposed therapeutics. DESIGN: Participants played a video game that delivered gunfire-like sound through headphones as part of a target practice game. Effects were measured using audiometric threshold evaluations and distortion product otoacoustic emissions (DPOAEs). The sound level and number of impulses presented were sequentially increased throughout the study. STUDY SAMPLE: Participants were normal-hearing students at the University of Florida who provided written informed consent prior to participation. RESULTS: TTS was not reliably induced by any of the exposure conditions assessed here. However, there was significant individual variability, and a subset of subjects showed TTS under some exposure conditions. CONCLUSIONS: A subset of participants demonstrated reliable threshold shifts under some conditions. Additional experiments are needed to better understand and optimize stimulus parameters that influence TTS after simulated impulse noise.